Systematic review of the recent evidence for the efficacy and safety of chlorambucil in the treatment of B-cell malignancies. Issue 4 (2nd April 2016) - Lepretre, Stéphane; Dartigeas, C.; Feugier, P.; Marty, M.; Salles, G.
Abstract: Emergence of new agents has deeply modified treatment options and the role of chlorambucil (CLB) in B-cell malignancies. We conducted a systematic review of prospective, randomized, controlled trials (RCTs) investigating the benefits and harms of CLB used alone or in combination with other treatment in patients suffering from chronic lymphocytic leukemia (CLL), low-grade non-Hodgkin lymphoma (NHL) or Waldenström macroglobulinemia (WM). For CLL, review of the nine RCTs showed that the main advantage of CLB is its low toxicity in comparison with purine nucleoside analogs like fludarabine in either CLL or NHL. In CLL, the major disadvantage is the very low rate of complete response, except when combining an anti-CD20 antibody. For B-cell lymphoma and WM, six RCTs were summarized. Results according to the usual criteria are presented and the role of CLB, used mostly in combination with an anti-CD20 antibody, is discussed for each indication, in particular for unfit patients.